Preclinical Toxicity and Safety of MM-129-First-in-Class BTK/PD-L1 Inhibitor as a Potential Candidate against Colon Cancer - Justyna Magdalena Hermanowicz; Bartlomiej Kalaska; Krystyna Pawlak; Beata Sieklucka; Joanna Miklosz; Mariusz Mojzych; Dariusz Pawlak (MDPI AG, 2021)
MM-129 is a novel inhibitor targeting BTK/PI3K/AKT/mTOR and PD-L1, as it possesses antitumor activity against colon cancer. To evaluate the safety profile of MM-129, we conducted a toxicity study using the zebrafish and rodent model. MM-129 was also assessed for pharmacokinetics features through an in vivo study on Wistar rats. The results revealed that MM-129 exhibited favorable pharmacokinetics with quick absorption and 68.6% of bioavailability after intraperitoneal administration. No serious adverse events were reported for the use of MM-129, confirming a favorable safety profile for this compound. It was not fatal and toxic to mice at an anticancer effective dose of 10 μmol/kg. At the end of 14 days of administering hematological and biochemical parameters, liver and renal functions were all at normal levels. No sublethal effects were either detected in zebrafish embryos treated with a concentration of 10 μM. MM-129 has the potential as a safe and well-tolerated anticancer formulation for future treatment of patients with colon cancer.